PENGARUH EMPATI TERHADAP PERILAKU PROSOSIAL DALAM BERBAGI ULANG INFORMASI ATAU RETWEET KEGIATAN SOSIAL DI JEJARING SOSIAL TWITTER - Rr. Sukma Dian Puspita; Gumgum Gumelar (Program Studi Psikologi Fakultas Pendidikan Psikologi Universitas Negeri Jakarta, 2014)
Abstract This study was conducted to determine the effect of empathy to pro-social behaviour in repeated share information or retweet social activities at social network twitter. The methods was used in this research is quantitative approach. Sampling techniques are using nonprobability sampling technique with kind incidental sampling techniques. The sample was used in this study amounted to 138. Data analysis techniques are use to test the hypothesis is a simple regression test which using SPSS version 16.00. Based on the counting result value F is 185.409 with value of significance is 0.000. The regression similarity of Y= 24.094 + 0.591X and great influence (R Square) a variable empathy to prososial behavior is 0.577, which means that empathy affect the behavior of prososial as much as 57.7% and the rest 42.3% is affected by another factors. Therefore, Ho denied and Ha accepted so it can be concluded that there is a significant positive influence of empathy to the behavior of prososial in sharing information or social activity in a retweet social networking twitter. Keywords: Empathy, Prososial Behavior, Social Networking Twitter